Pembinaan moral dalam tafsir al-isra ayat 23 - Nahilah, Hilyatun (Maliki Interdisciplinary Journal, 2024)
The Islamic religion has regulated life as well as possible. Civilized Muslims are those who always try to be devout. One form of Allah’s prohibition is the prohibition on approaching the act of adultery, this means that not only the act of adultery is prohibited, but also things that can lead to this act. This article discusses the Tafsir of Surah al-Isra’ verse 32, linguistic analysis, applicable jurisprudence laws, wisdom in establishing laws, as well as moral learning in the interpretation of the Al-Qur’an Surah al-Isra’ verse 32, which can be prevent someone from various deviant behavior. The author uses the library research method. Then the data sources are classified into two parts, the main data sources include books of interpretation of the Al-Qur’an, while secondary data sources include books and scientific journals. Then, by collecting data that is deemed necessary, to be written in this article, a conclusion is finally drawn. The results of the research show that in the stipulation of the Shari’a prohibiting adultery, Allah SWT shows that adultery begins when a person commits a disobedience to Allah SWT. This indirectly contains a moral message that must be applied by a person in order to avoid committing adultery, so that he is expected to become a good servant. devout.